AI Based Applications to Foster Pronunciation Accuracy - Ahsin Fahmi Mubarok; Mochammad Abdullah Salim; Zhenita Deliany (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2025)
Accurate pronunciation is fundamental to effective communication. Meanwhile, many EFL learners struggle due to limited exposure and first language interference. This study investigates the effectiveness of two AI-based applications ElsaSpeak and ElevenLabs in improving English pronunciation accuracy among Indonesian vocational students. Employing a comparative descriptive method, 20 first-semester students were divided into two groups based on equal pre-test scores. Each group received three pronunciation practice sessions using one of the tools. Post-test results showed significant improvement in both groups, with ElsaSpeak yielding slightly higher gains due to its real-time, phoneme-level feedback. Learner responses confirmed positive experiences with both tools, although ElsaSpeak was preferred for its interactive features. These findings suggest that AI-assisted pronunciation tools can serve as effective supplements to traditional instruction by offering individualized, flexible learning. The study highlights the value of integrating such technologies into EFL pedagogy to enhance pronunciation development and promote learner autonomy.